Rare earth elements in aeolian loess sediments from Menyuan Basin, northeastern Tibetan plateau: Implications for provenance - Shi, Yunkun; E, Chongyi; Peng, Qiang; Zhang, Zhaokang; Zhang, Jing; Yan, Wenting; Xu, Chunxia (Frontiers in Environmental Science, 2023)
Aeolian loess is a widespread deposit in mid-latitude arid and semiarid regions that has been extensively investigated in arid Central Asia and the Chinese Loess Plateau. The northeastern Tibetan Plateau is crucial to the release, transport, and accumulation of aeolian sediments because of its vast environmental differences, but relatively little research has been conducted on the loess here. To further deepen our understanding of the loess source in this region, we selected the Menyuan Basin as the study area for this loess tracing research. Through our investigation of the indicators and distribution characteristics of rare earth elements in the Yahecun (YHC) loess-paleosol profile of the Menyuan Basin, the following conclusions were drawn: 1) the indices and distribution curves of rare earth elements in the diverse strata of the YHC profile were not significantly distinct and were comparable to those of loess from other locations in northwestern China, revealing a general association with loess in arid northwestern China; 2) the influence of chemical weathering and particle diameter on rare earth elements in the loess of the study area was minimal, and Menyuan loess rare earth elements contained considerable information regarding their source; and 3) a comparison of the (La/Yb)N, δEu, (La/Sm)N, and (Gd/Yb)N parameters of potential source areas indicates that arid Central Asia, dominated by the Qaidam Desert, is the primary source area of the Menyuan loess, and dust particles released from these deserts are transported to the Menyuan Basin by the Westerlies and deposited to form loess. Additionally, the Badain Jaran Desert is an essential source of material for the Menyuan loess by winter winds, and some Tengger Desert materials are also transported to the Menyuan Basin by winter winds, but the material transported from the Tengger Desert has a negligible contribution.